The Analysis of Flouting Maxim in “UP!” Movie - Devian Try Gustary; Suciati Anggraini (Jurnal Lingua Idea, 2021)
This study focuses on flouting maxim uttered by characters in “UP!” movie. This study is aimed at analyzing types of flouting maxims performed by the characters and describing strategies of flouting maxims uttered by characters in the movie. In analyzing the types and strategies of flouting maxims of characters, Cutting’s theory (2002) is used. The researcher also employed qualitative research method to collect the data. The result showed two important findings. First, it was found that there are four types of flouting maxims in the movie. They are flouting maxims of quantity, quality, relation and manner. Flouting maxims of quality was rank first because the characters deliberately say something that is believed to be false. Second, there are ten strategies of flouting maxims found in the movie. They are giving too little information, giving too much information, hyperbole, metaphor, irony, banter, sarcasm, being irrelevant, changing the topic and being obscure. The occurrence of the strategy that mostly used to flout maxims was giving too much information. It happened because the characters always give too much information than what is required.